Можливість рециклінгу будівельних відходів в Україні - Шпакова, Г. В. (Ways to Improve Construction Efficiency, 2012)
The article describes the main types of construction waste, analyzed the experience of recovery and recycling of building waste in the world's countries and also investigated the state of the problem of processing of construction waste in Ukraine, suggested some steps to solve the problem.